Evaluation of Chronotype Among Children and Associations With BMI, Sleep, Anxiety, and Depression - Eid, Bassam; Bou Saleh, Mary; Melki, Imad; Torbey, Paul-Henry; Najem, Joelle; Saber, Maroun; El Osta, Nada; Rabbaa Khabbaz, Lydia (Frontiers in Neurology, 2020)
Objectives: to evaluate possible associations between chronotype, weight, sleep problems, anxiety and depression among children from 6 to 12 years of age. Method: 100 children aged between 6 and 12 years were randomly recruited in 5 pediatrician clinics in the capital city of Beirut, Lebanon. The protocol was approved by the ethics committee of Saint-Joseph University and Hotel-Dieu Hospital and an informed written formal consent was obtained from one of the parents. The Sleep Disturbance Scale for Children (CCTQ), the Revised Child Anxiety and Depression Scale (RCADS)-Parent version and the Children’s ChronoType Questionnaire (CCTQ) were used. Results: the majority of the sample (47%) presented an intermediate chronotype. There was a shift toward evening chronotype with increased age and a significant association between electronic devices use and an evening chronotype. Higher sleep disturbances were also observed among children with an evening chronotype. In particular, disorders of initiating and maintaining sleep, excessive somnolence, non-restorative sleep and total SDSC were significantly higher among evening type children in our study. Finally, major depression scores were significantly higher among children with an evening chronotype Conclusions: Several findings observed in this study are of importance in explaining factors associated to circadian rythm disctubances in children. Two important future perspectives can be highlighted: limiting electronic devices use among children in an effort to reduce circadian rythm disturbances and identifying and treating sleep problems associated with eveningness, taking into account the possible presence of major depression among this population.